How Campaign Drive Donation Behavior and E-wom: SOBC Conceptual Framework - Faudrya , Christita; Putra, Gatum Ananta; Pratama, Moch. Dendhy Putra Andreza; Hartini, Sri (Jurnal Economic Resource, 2025)
This study examines the factors influencing donation activities on the Kitabisa.com platform by analyzing data from 120 respondents collected through Google Forms and processed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results show that the initiator's reputation, campaign popularity, and credibility significantly influence donor behavior, highlighting the crucial role of credibility in determining the success of crowdfunding campaigns. The study applies the Stimulus-Organism-Behavior-Consequence (SOBC) theory to understand the psychological mechanisms behind donation behavior, emphasizing the interplay between credibility and campaign popularity in shaping donor decisions. From a practical standpoint, these findings provide valuable insights for crowdfunding platforms, suggesting that enhancing credibility and increasing campaign popularity can drive higher donor engagement. Furthermore, policymakers and campaign initiators can leverage these insights to design more effective fundraising strategies. However, the study has several limitations, including its focus solely on Kitabisa.com, the use of non-probability sampling methods, and the reliance on subjective e-WOM measurements, which may limit the generalizability of the findings. Future research could explore other crowdfunding platforms, incorporate probability sampling techniques, and employ more objective e-WOM measures to enhance the robustness of the results.